Career Consultation as an Intervention Strategy in Alleviating Family’s Mental Health: A Case Study on Students with Disabilities - Mohd Noor, Norhayati; Mohamed, Maslawati; Nor, Azmawaty Mohamad; Abdullah, Rohaya (Penerbit Universiti Sains Malaysia, 2019)
Relevant information is critical in assisting families and teachers to help students with disabilities in planning their careers appropriate for their capabilities and abilities. Having the correct information and understanding will alleviate the psychological burden faced by family members in dealing with children with special educational needs. This study aimed to explore the knowledge and understanding of parents with special needs on the job marketability of their children. This qualitative study was conducted with 11 multi-case multi-site families of special education students. The consultation process for phase one involved consultations conducted by special education teacher trainees. The second phase of consultation and collaborative process involved students and special education students with undergraduate education guidance and counselling. The verbatim data were analysed using NVivo 11. The study showed that families still lack knowledge in the marketability of their special needs children particularly due to the limited information channel. The findings showed that knowledge on job marketability can help the parents plan their special needs children’s job marketability, which in turn, would directly contribute to the family wellbeing.